The Utilization of Information Technology for the Professional Development of Islamic Education Teachers in Indonesia - M. Ikhwan; Muhammad Fuadi; Mailizar Mailizar; Misbahul Jannah (Universitas Muhammadiyah Malang, 2023)
The professional development of Islamic Religious Education (PAI) teachers is crucial to enhancing the quality of PAI learning in schools. One effective means to support their professional growth is through the utilization of technology as a learning medium and information source. This article aims to explore the use of technology by PAI teachers in their professional development, focusing on three key aspects: (1) The Importance of Integrating Technology in Teacher Professionalism; (2) Types and Functions of Technology Used by PAI Teachers; (3) Challenges Encountered by PAI Teachers in Advancing Professionalism through Technology. The research methodology used the qualitative method with the literature review approach, encompassing data collection and analysis from diverse sources such as journals, books, reports, and websites. The findings reveal that PAI teachers in Indonesia employ various technologies, including computers, laptops, smartphones, tablets, internet connectivity, social media platforms, applications, and software, for multiple purposes like information retrieval, communication, collaboration, content creation, presentation, and assessment of learning. The use of technology among PAI teachers yields several advantages, including the enhancement of knowledge, skills, motivation, creativity, networking opportunities, and learning resources. However, they face challenges related to limited infrastructure, access, costs, and support. Moreover, there's a lack of readiness, competence, and awareness regarding ethics and security among these educators. PAI teachers encounter difficulties, obstacles, and risks such as network disruptions, viruses, malware, spam, phishing, hacking, cyberbullying, and plagiarism. The challenges of utilizing technology for teacher professional development encompass skills, attitudes, infrastructure, and ethical considerations. Therefore, PAI teachers must possess adequate competence and readiness to integrate technology into their professional development.